(untitled) - Epstein, Gene (Hoboken, N.J., 2006)
ene Epstein knows a thing or two about economic data. Before becoming the Economics Editor for Barron's in 1993, he was a senior economist at the New York Stock Exchange. Now in Econospinning, Epstein supplies readers with a book that attempts to cut through the veil of economic misinformation commonly reported in today's media.
Keywords: Mass media, Journalism,United States,Thông tin đại chúng,Báo chí,Hoa Kỳ; Objectivity,Objectivity,Economic policy,Press coverage,Khách quan,Khách quan,Chính sách kinh tế,Họp báo; United States,United States,Hoa Kỳ,Hoa Kỳ